Forest covers, land fire hotspots, and atmospheric pollutions (CO, SO2) in the lower Batanghari River Basin landscape during dry season (June-August 2021) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wibowo AA, Basukriadi A, Nurdin E. 2021. Forest covers, land fire hotspots, and atmospheric pollutions (CO, SO2) in the lower Batanghari River Basin landscape during dry season (June-August 2021). Biodiversitas 22: 5678-5687. Land fire is a major threat to the intact forest in Indonesia, including the rainforests of Sumatra. Land fires are caused by several factors, ranging from deforestation, slash and burn to farm, and also weather where land fires occur during dry seasons. Land fires that occur in forests can release significant amounts of atmospheric pollution in the form of CO and SO2 emissions. Since there is a paucity of information about land fire hotspot distribution and atmospheric pollution in Sumatra’s forest, this study aims to assess the distribution and impacts of land fires within the lower Batanghari forest landscape on atmospheric pollution during the dry season from June to August 2021. The study was conducted in 15 sampling locations covering three districts in the lower Batanghari landscape. The method uses a coupled ground-based and remote sensing measurement. For ground-based measurement, the CO and SO2 emissions were determined based on in-situ observation of burned biomass in the field and calculation using Seiler and Crutzen equation. While the land fire hotspots were detected using combinations of VIIRS (Visible Infrared Imaging Radiometer Suite) and MODIS (Moderate-resolution Imaging Spectroradiometer) remote sensing sensors. The result shows that 65.85% of the land fires that happened in the lower Batanghari landscape occurred within forests. In West Tanjung Jabung District, 70.37% of land fires were observed within forests, in East Tanjung Jabung was 60% and 55.55% for Muaro Jambi District. The weekly land fires, CO, and SO2 emissions were high in June as the onset of dry season. In West Tanjung Jabung, this district has the highest weekly land fires, CO, and SO2 emissions. The ranges of CO and SO2 emissions when land fires occur were 200-350 ppbv and 1.5-2.75 ug/m3. The Principal Component Analysis confirms that the frequency of land fires was positively correlated with CO rather than SO2 emissions. This concludes the magnitude of land fires in forests that have the potential to release significant atmospheric pollutants.